Karakteristik Fisikokimia, Sensori, dan Respons Glikemik Flakes Tinggi Serat Berbasis Tepung Beras dan Tepung Kelapa: Physicochemical, Sensory, and Glycemic Response Characteristics of High-Fiber Flakes Formulated with Rice Flour and Coconut Flour - Risti Rosmiati; Esi Emilia; Nila Reswari Haryana; Hardi Firmansyah; Fathia Rahmadini; Henisah Pebrianti; Tiffany Nita Karina Ginting (Amerta Nutrition, 2025)
Background: Flakes are widely consumed cereals, but their formulation often produces high glycemic index (GI) values. Rice flour, a common base, may elevate postprandial glucose, while coconut flour, rich in dietary fiber, can lower glycemic response and improve nutritional value. Objectives: This study aimed to identify the best formulation of rice flour–coconut flour flakes and to evaluate the glycemic index and glycemic load of the selected formula. Methods: Flakes were prepared in three ratios: F1 (75:25), F2 (50:50), and F3 (25:75). Proximate composition, dietary fiber, physical properties, and sensory attributes were assessed to determine the selected formula. Glycemic index testing was performed on 10 healthy adults according to Indonesian National Agency of Drug and Food Control (BPOM) guidelines, using glucose as reference. Capillary blood glucose was measured at 0–120 minutes, and glycemic load was calculated from GI and available carbohydrate. Results: Increasing coconut flour significantly raised dietary fiber (p-value=0.000), with F3 showing the highest content (48.51%). Sensory evaluation indicated F2 (50:50) was most acceptable, with higher scores for aroma, texture, and overall liking. F2 also showed moderate resistance compared to F1 and F3. GI testing of F2 yielded a low GI value of 49, while the glycemic load was also low at 4.9 per serving. Conclusions: The incorporation of coconut flour improved the nutritional and functional quality of rice flour flakes. F2 (50:50) was the best formulation, producing flakes with favorable acceptance and low glycemic response, supporting its potential as a healthier cereal product.